Capacity analysis of three-node wireless Gaussian relay channel - ZHANG Yuan; GAO Xi-qi (Tongxin xuebao, 2006)
The capacity of three-node wireless relay channel was analyzed. While previous research work showed how parameters like relay numbers, antenna numbers and fading affected the capacity, focused on the impact of relay position. By analysis results, there were three modes that the capacity will follow: with relay moving from source toward destina- tion, the capacity can decrease （mode C1）, or increase （mode C3）, or decrease after increasing （mode C2）. A numerical example was given to verify the theory.